Pegaruh Kompotensi Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan PT. Bina San Prima Makassar - Dicky Zulkarnain Rona Gah (Jurnal Online Manajemen ELPEI, 2021)
The Effect of Competence, Work Environment and Compensation on Employee Performance at PT. Bina San Prima Makassar "is the result of a quantitative study that aims to answer questions about competence, work environment and compensation for employee performance at PT. Bina San Prima Makassar. The research methodology used is quantitative research using survey methods. The sampling technique used simple random sampling with a total of 5 0 respondents. The technique uses data using a questionnaire which is processed using SPSS version 2 1 . Data analysis using multiple linear regression. The results of the study show that competence has a partial effect on the PERFORMANCE of employees at PT. Bina San Prima Makassar, this is evidenced by a t-count value of 3.287 and a significance value of 0.00 2. Work environment has a partial effect on the performance of employees of PT. Bina San Prima Makassar, this is evidenced by a calculated t value of 3.334 and a significance value of 0.002. Compensation has a partial effect on the performance of employees of PT. Bina San Prima Makassar, this is evidenced by the calculated t value of 3,520 and a significance value of 0.001. Meanwhile, based on the results of simultaneous test statistical calculations, it can be seen that competence, work environment and simultaneously influence PT. Bina San Prima Makassar, this is evidenced by a calculated F value of 10.685 and a significance value of 0.000 and a coefficient of determination of 0.3 7 2 which means that employee performance can be explained by competency, work environment and compensation variables, amounting to 3 7 , 2% while the rest by other variables that are not in this study.